Analisis Strategi Kualitas Pelayanan Publik Pada Perusahaan Jasa - Arif Ismunandar (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2020)
Satisfaction of the quality of service to consumers can provide value for companies to get sympathy and respect from consumers. Often companies are indifferent to the services provided, the lack of friendliness, smiles and greetings that are a little forced will affect the quality of service. This paper describes the service strategy in service companies. The presentation of this paper is based on analysis of library data with descriptive models. From the results of the discussion it can be concluded that the services provided by the service company authority cannot be separated from the service standards set by the company itself. Companies engaged in the service sector knowingly that consumers are their target market. Service improvement strategies can be identified through improving the quality of management, the quality of human resources, the quality of services and the quality of infrastructure.